2005
DOI: 10.1210/en.2005-0451
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Strongly Inhibits Human Osteoclast Formation

Abstract: Prostaglandin E(2) (PGE(2)) enhances osteoclast formation in mouse macrophage cultures treated with receptor activator of nuclear factor-kappaB ligand (RANKL). The effects of PGE(2) on human osteoclast formation were examined in cultures of CD14(+) cells prepared from human peripheral blood mononuclear cells. CD14(+) cells differentiated into osteoclasts in the presence of RANKL and macrophage colony-stimulating factor. CD14(+) cells expressed EP2 and EP4, but not EP1 or EP3, whereas CD14(+) cell-derived osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 36 publications
2
64
1
Order By: Relevance
“…In addition, previous data [2] also showed that PGE 2 strongly inhibits bone resorption. This concurs with the data of Take et al [38] which demonstrate that PGE 2 could act directly as an inhibitor of osteoclastogenesis by its interaction on osteoclast precursors, and of Raisz et al [39] which showed that high concentrations of PGE 2 favour bone deposition, as well as others showing that high levels of PGE 2 induce collagen type I production in OA human osteoblasts [40] and IGF-1 [12] synthesis. However, although RANKL-independent mechanisms are involved in the control of bone remodelling, RANKL-dependent modulation remains the major pathway involved in such remodelling.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, previous data [2] also showed that PGE 2 strongly inhibits bone resorption. This concurs with the data of Take et al [38] which demonstrate that PGE 2 could act directly as an inhibitor of osteoclastogenesis by its interaction on osteoclast precursors, and of Raisz et al [39] which showed that high concentrations of PGE 2 favour bone deposition, as well as others showing that high levels of PGE 2 induce collagen type I production in OA human osteoblasts [40] and IGF-1 [12] synthesis. However, although RANKL-independent mechanisms are involved in the control of bone remodelling, RANKL-dependent modulation remains the major pathway involved in such remodelling.…”
Section: Discussionsupporting
confidence: 91%
“…Daggers indicate a significant difference between the PSL-treated and untreated OP cells ( osteoclastogenesis from BM cell cultures. This suggests that PSLs also affect the functions of osteoblasts and stromal cells in a paracrine manner because they have receptors for both TGF-b1 and PGE 2 (45,46). PSLs activate p44/p42 ERK but not p38 MAPK in primary cultured rat microglia (16) and macrophages (15).…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that L-OA, but not H-OA, osteoblasts enhanced the formation of osteoclasts (20). A direct effect of PGE 2 on osteoclastogenesis is also possible, since Take et al (44) recently demonstrated such an effect on osteoclasts, which occurred through interactions with PGE 2 on its specific receptors.…”
Section: Discussionmentioning
confidence: 99%